THERMAL DECOMPOSITION OF UROTROPINE COMPLEXES WITH NICKEL AND COBALT CHLORIDES - D. V. Golubev; E. V. Savinkina; A. .. Al-Khazraji; M. N. Davydova (Тонкие химические технологии, 2017)
Complex compounds NiCl2·2HMTA·10H2O (1), CoCl2·2HMTA·10H2O (2), CoCl2·HMTA·4.5H2O (3) were prepared by the reaction of nickel(II) and cobalt(II) chlorides with urotropine (HMTA). Compounds 1 and 2 are isostructural, their structure corresponds to the earlier studied crystal structure [Ni(H2O)6]Cl2·4H2O·2HMTA. Thermal destruction of the complex compounds 1-3 was studied by TGA and high-temperature IR-spectroscopy. The TGA curve for compound 1 shows stepwise mass loss caused by two-stage loss of all water molecules (up to 170°C) and one urotropine molecule (up to 270°C) followed by decomposition of NiCl2·HMTA. The X-ray diffraction pattern of the resulting solid shows no reflections typical for the metal and its simplest nitrogen-, carbon- and chlorine-containing compounds. Thermal decomposition of сompounds 2 and 3 proceed similarly, but water is removed in one stage. IR spectra, which were recorded at high temperature (up to 220-230°C) show gradual decrease of intensity of the bands assigned to vibrations of water molecules. The bands of the methylene groups of urotropine do not change on heating. However, the bands of the C-N vibrations shift from ~1050 and ~1008 cm-1 in the spectra of urotropine and [M(H2O)6](HMTA)2Cl2·4H2O to 1015-1019 and 984-995 cm-1, respectively, indicating coordination of urotropine molecules instead of the removed water molecules. The long-wave IR spectra for NiCl2·6H2O and compound 1 at ambient temperature show bands of Ni-O stretching vibrations and O-Ni-O bending vibrations. After heating 1 at 115° C, bands of Ni-N and Ni-Cl appear, which indicates the coordination of urotropine molecules and chloride ions after the removal of outer-sphere and inner-sphere water molecules.